Managerial communication : strategies and applications / Larry R Smeltzer, Geraldine E. Hynes, Donald J. Leonard - Smeltzer, Larry R.
Focusing on skills and strategies that managers need in workplace, this work helps the managers learn the skills and strategies necessary for successful and effective business communication.